Comparison of human erythrocyte purine nucleotide metabolism and blood purine and pyrimidine degradation product concentrations before and after acute exercise in trained and sedentary subjects - Dudzinska, Wioleta; Suska, M.; Lubkowska, A.; Jakubowska, K.; Olszewska, M.; Safranow, K.; Chlubek, D. (The journal of physiological sciences, 2018)
This study aimed at evaluating the concentration of erythrocyte purine nucleotides (ATP, ADP, AMP, IMP) in trained and sedentary subjects before and after maximal physical exercise together with measuring the activity of purine metabolism enzymes as well as the concentration of purine (hypoxanthine, xanthine, uric acid) and pyrimidine (uridine) degradation products in blood. The study included 15 male elite rowers [mean age 24.3±2.56 years; maximal oxygen uptake (VO2max) 52.8±4.54 mL/kg/min; endurance and strength training 8.2±0.33 h per week for 6.4±2.52 years] and 15 sedentary control subjects (mean age 23.1±3.41 years; VO2max 43.2±5.20 mL/kg/min). Progressive incremental exercise testing until refusal to continue exercising was conducted on a bicycle ergometer. The concentrations of ATP, ADP, AMP, IMP and the activities of adenine phosphoribosyltransferase (APRT), hypoxanthine-guanine phosphoribosyltransferase (HGPRT) and phosphoribosyl pyrophosphate synthetase (PRPP-S) were determined in erythrocytes. The concentrations of hypoxanthine, xanthine, uric acid and uridine were determined in the whole blood before exercise, after exercise, and 30 min after exercise testing. The study demonstrated a significantly higher concentration of ATP in the erythrocytes of trained subjects which, in part, may be explained by higher metabolic activity on the purine re-synthesis pathway (significantly higher PRPP-S, APRT and HGPRT activities). The ATP concentration, just as the ATP/ADP ratio, as well as an exercise-induced increase in this ratio, correlates with the VO2max level in these subjects which allows them to be considered as the important factors characterising physical capacity and exercise tolerance. Maximal physical exercise in the group of trained subjects results not only in a lower post-exercise increase in the concentration of hypoxanthine, xanthine and uric acid but also in that of uridine. This indicates the possibility of performing high-intensity work with a lower loss of not only purine but also pyrimidine.